Terminology of Structuralism Field and Establishing its Concepts - Abu Seksaka, Hanan ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2021)
This research aims to identify the origins of the terminology of the structural field and to establish its concepts in the Western Space, their formulation mechanism in the Arab Space and the reasons of their multiplicity. This paper reached a number of results, the most important ones are; the terms and concepts of the structural field in Western space, some of their origins descend to other non-linguistic fields, including philosophy, mathematics, psychology, etc. The Arab field, the mechanisms for developing terminology of this field varied between translation, coining, and loanwords. Terminology varied according to multiplicity of their setting mechanisms, between translated, coined, and loanwords. Translated terms diversify according to varying the criteria of setting the term, translators and who come first to give them such criteria. Some of loanwords diverse according to the diverse of their source languages. Terminology multiplicity diversify according to their transferees and diversify according to the transferee themselves in the book itself. The reasons behind this are either taking into account the backgrounds of readers, or the transferee’s confusion on a term, which are found in theoretical or applied books. Concerning documenting common and accepted synonyms for the term is the norm of most dictionaries.